1997
DOI: 10.1007/bf02765838
|View full text |Cite
|
Sign up to set email alerts
|

Treatment variables in relation to oocyte maturation: Lessons from a clinical micromanipulation-assisted in vitro fertilization program

Abstract: Objective: In an effort to understand the mechanism underlying the improved pregnancy rate observed in IVF cycles when gonadotropin-releasing hormone analogues ( GnRH-a )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Avrech et al demonstrated that ICSI cycles yielding higher response rates and greater numbers of oocytes were associated with more immature oocytes (11). The present patient certainly had a high response rate, averaging 28 oocytes per cycle, whereas the average 28-year-old woman undergoing ICSI in our practice produced 16 oocytes per cycle (Mann-Whitney: P¼.02).…”
Section: Discussionmentioning
confidence: 61%
“…Avrech et al demonstrated that ICSI cycles yielding higher response rates and greater numbers of oocytes were associated with more immature oocytes (11). The present patient certainly had a high response rate, averaging 28 oocytes per cycle, whereas the average 28-year-old woman undergoing ICSI in our practice produced 16 oocytes per cycle (Mann-Whitney: P¼.02).…”
Section: Discussionmentioning
confidence: 61%
“…Although complete failure of oocytes to complete meiosis maturation during assisted conception cycles is rare, occasional and repetitive maturation resistance does occur in infertile patients (Avrech et al, 1997;Bar-Ami et al, 1994;Beall et al, 2010;Heindryckx et al, 2011). Patients presenting with an abnormally high number of immature oocytes at retrieval show a high probability of exhibiting maturation resistant oocytes, although the influence of such an event on the nuclear maturation competence, as well as on the subsequent pregnancy outcomes of these patients, have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 20%–30% of oocytes collected for IVF are meiotically immature at the time of oocyte retrieval,[ 9 ] and this is probably because of the stimulation of multiple follicles. When the percentage of incompetent oocytes was ≥25%, most of the IVF outcomes were markedly reduced.…”
Section: Discussionmentioning
confidence: 99%